Analysis Promotion Efforts of Exclusive Breastfeeding (A qualitative study in Puskesmas Pati II) - Ari Prasetyowati, Tri (Universitas Negeri Semarang, 2019)
The benefits of exclusive breastfeeding in accordance with one of the objectives of the Millennium Development Goals (MDGs) of reducing child mortality and improving maternal health. The promotional efforts of exclusive breastfeeding can analisys approach musty system consisting of input, process aspects, and aspects of the output. The research objective to analyze the promotional efforts of exclusive breastfeeding in Puskesmas Pati II. This type of research is a qualitative which focused on efforts to promotion of exclusive breastfeeding. The informants are determined by purposive sampling and snowball sampling. Data collection techniques with in-depth interviews. Input aspect is human resources midwives, the source of funds of the government ie BOK funds, availability of infrastructure adequate promotion of exclusive breastfeeding, and for the availability of SOP promotion of exclusive breastfeeding need reconsideration. Aspects of the process carried out classroom activities pregnant women and mothers, training of exclusive breastfeeding by midwives, nutrition and health cadres, networking, monitors the evaluation conducted regularly by midwives in coordination with DKK and Puekesmas, and the obstacles faced when promoting exclusive breastfeeding, Aspects of output is less than optimal because there is still no village Puskesmas Pati II failed to reach the target coverage exclusively breastfed. Health Department needs to make clear SOPs to support the promotion of exclusive breastfeeding. Puskesmas need to make special recruitment of health promotion at the health center.Ã‚Â Kata kunci : ASI eksklusif, upaya promosi